A serious game for understanding ancient seafaring in the Mediterranean Sea - Philbin-Briscoe, Oliver; Simon, Bart; Mudur, Sudhir; Poullis, Charalambos; Rizvic, Selma; Boskovic, Dusanka; Liarokapis, Fotis; Katsouri, Irene; Demesticha, Stella; Skarlatos, Dimitrios (My University, 2017)
Commercial sea routes joining Europe with other cultures are vivid examples of cultural interaction. In this work, we present a serious game which aims to provide better insight and understanding of seaborne trade mechanisms and seafaring practices in the eastern Mediterranean during the Classical and Hellenistic periods. The game incorporates probabilistic geospatial analysis of possible ship routes through the re-use and spatial analysis from open GIS maritime, ocean, and weather data. These routes, along with naval engineering and sailing techniques from the period, are used as underlying information for the seafaring game. This work is part of the EU-funded project iMareCulture whose purpose is in raising the European identity awareness using maritime and underwater cultural interaction and exchange in the Mediterranean sea.
Keywords: Games; Marine vehicles; Geospatial analysis; Tools; Cultural differences; Ports (Computers); Meteorology; Archaeology; Geographic information systems; History; Naval engineering; Ships